Peningkatan Hasil Pembelajaran Jarak Jauh Matematika Materi Lingkaran Melalui Video Pembelajaran Berbasis Aplikasi Filmora - Endang Rijati (CENDEKIA, 2021)
This study aims to improve the results of distance learning mathematics circle material for students in class VIII A SMP Negeri 1 Lamongan through learning video media based on the Filmora application. The subjects in this study were students of class VIII A SMP Negeri 1 Lamonngan, totaling 32 students. The object of this research is mathematics subject matter in circle. Data collection methods used in this study were observation and tests with research instruments, namely observation sheets and evaluation questions. The data analysis technique used in this research is descriptive qualitative data analysis and quantitative descriptive. The results showed that using video learning media based on the Filmora application can improve the distance learning outcomes of class VIII A students of SMP Negeri 1 Lamongan in the algebraic form material for the 2020/2021 school year. This is evidenced by the increase in test scores from each cycle. This increase was marked by an increase in learning completeness 49% in the first cycle with an average value of 71.01 in the good enough category and in the second cycle it increased to 91% with an average value of 90.23 in the good category.